Dynamic association between socio-economic, environmental and logistic operations: Evidence from SSA BRI host countries - Ali Aden, Waiss; Zheng, Jianfeng; Almoshageh, Meshal; Ullah, Irfan; Aziz, Qaiser; Jamal, Arshad (Frontiers in Environmental Science, 2022)
This study examines the connection among green logistic operations, countries-level economic, environmental, and social indicators in Sub-Saharan Africa (SSA) Belt and Road Countries. Using the system generalized method of moments (S-GMM) estimator, this study analyses annual data from 2008 to 2018 and offers three key findings. First, economic indicators China’s foreign direct investment (FDI), trade openness and economic output) are positively associated with green logistic operations. Second, logistics are positively correlated with renewable energy while inversely correlated with carbon emissions. Third, social indicators are also directly associated with green logistic operations measured through health expenditure and institutional quality. Lastly, information communication technology also spurs green logistic operations. Manifestly, Chinese outbound FDI in SSA substantially improved the quality of their logistics in terms of infrastructure, cost, time, customs services, tracking, and the consistency of international shipments. These findings show that green logistics provide adequate infrastructure, and supply chain partners share information more frequently, increasing trade volume, growth potential, and environmental sustainability. Similar results are also endorsed using a feasible generalized least square (FGLS) estimator and suggest that SSA should take effective measures to improve their logistics operation.